Effects of Rosmarinus officinalis Essential Oil and Verbascum cheiranthifolium and Chrysanthemum cinerariaefolium Extracts to Greenhouse Whitefly (Trialeurodes vaporariorum) - Basri ŞANLI; Arif ŞANLI; İsmail KARACA (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2020)
In this study, effects of essential oil of rosemary (Rosmarinus officinalis) and plant extracts of mullein (Verbascum cheiranthifolium) and pyrethrin (Chrysanthemum cinerariaefolium) against greenhouse whitefly (Trialeurodes vaporariorum) on tomato plant (Lycopersicon esculentum) has been researched. In the study, 5 different concentrations of essential oils and plant extracts prepared and applied in two different methods as spraying and dipping to tomato plants. After 24 hours counts, maximum mortality rates were 46.3% for rosemary EO and 0% for mullein and pyrethrin applicaitons. After 72 hours counts, mortality rates were 42.9% for mullein, 69.3% for pyrethrin and 100% for rosemary applications. After 120 hours counts, mortality rates were 74.1% for mullein, 100% for pyrethrin and 100% for rosemary applications.